ANALISIS KINERJA PENGELOLAAN KEUANGAN DAERAH DAN PENGARUHNYA TERHADAP TINGKAT KEMISKINAN DI KOTA PEKANBARU - Mizkan, Hendra; Kamaliah, Kamaliah; Agusti, Restu (SOROT, 2015)
Abstract The purpose of this research is to know if the management of finance Pekanbaru city was managed well, effective and efficient and if the management of finance is influenced toward the degree of society poverty Pekanbaru city. This research was conducted by using quantitative descriptive analysis method and double linear regression analysis. The data was collected by finding references and the field research was conducted in Development Planning Agency at Sub-National Level (Bappeda) Pekanbaru city, Central Bureau of Statistics (BPS) Pekanbaru city and Local Revenue Offices (Dispenda) Pekanbaru city. The result of research shows that in the seventh years lately (2006-2012) the degree of finance autonomy still in criterion “less” with the correlation pattern with center government has characteristic “instructive”, the degree of finance competence still in criterion “less”, the finance activity is included in criterion “good”, the finance effectivity is included in effective criterion, the finance efficiency is included in criterion “efficient”, the growth of finance is included in criterion “good”, whereas the degree of poverty is not taking down thoroughly. Neither in partial nor in simultaneously the management of finance is not influenced significantly toward the degree of poverty in Pekanbaru city.